2015
DOI: 10.18632/aging.100772
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted antioxidant SkQ1 improves impaired dermal wound healing in old mice

Abstract: The process of skin wound healing is delayed or impaired in aging animals. To investigate the possible role of mitochondrial reactive oxygen species (mtROS) in cutaneous wound healing of aged mice, we have applied the mitochondria-targeted antioxidant SkQ1. The SkQ1 treatment resulted in accelerated resolution of the inflammatory phase, formation of granulation tissue, vascularization and epithelization of the wounds. The wounds of SkQ1-treated mice contained increased amount of myofibroblasts which produce ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…SkQ1 also prevented TNF-induced decomposition of VE-cadherin-containing contacts, following an increase in the permeability of endothelial cell monolayer [12]. SkQ1 also inhibited apoptosis of endothelial cells induced by high doses of TNF [28].…”
Section: Discussionmentioning
confidence: 99%
“…SkQ1 also prevented TNF-induced decomposition of VE-cadherin-containing contacts, following an increase in the permeability of endothelial cell monolayer [12]. SkQ1 also inhibited apoptosis of endothelial cells induced by high doses of TNF [28].…”
Section: Discussionmentioning
confidence: 99%
“…It seems attractive to develop a protocol that reduces its negative impact on proliferation. We cannot exclude that this side effect may be much stronger in the elderly, where proliferative and regenerative processes are retarded [63]. For example, it has been shown that in telomeraseknockout mice, the time necessary to recover renal function after I/R was longer than in agematched wild-type controls [64].…”
Section: Would Activation Of Autophagy Protect the Elderly?mentioning
confidence: 97%
“…And fibroblast dysfunction is linked to the overproduction of free ROS . Application of antioxidant or drugs with antioxidant properties could relieve the microenvironment of chronic inflammation, accelerate wound healing and alleviate scar formation on wounds . Similarly, classical traditional medicine, arsenic trioxide, could effectively inhibit the formation of rabbit ear scars through the overexpression of antioxidant genes …”
Section: Biotherapy For Inflammation In Hssmentioning
confidence: 99%